The Peruvian republican State and the jurisdictional expansion of the Lancasterian method in the towns near Lima, 1821-1840 - Huaraj Acuña, Juan Carlos (2018)
The public instruction since the installation of the Republic itself, was sponsored by the State itself. The affirmed is verified in detail through the various supreme decrees and legislative documentation referred to it. Initially, under the institutional sponsorship of the Public Beneficence, as well as of the regionals Prefects. In its crepuscular educational functions, the State was supported by clerical institutions, such as local parishes and dioceses. The Central (or Normal) Lancasterian College, represented a direct political creation of the historical period of the Protectorate. The aforementioned educational institution, under the direction of Pbro. José Francisco Navarrete, reached not only the goodwill and goodwill of the Supreme Government during successive governments, but that represented openly and without any doubt, the initial political alliance between the Peruvian Republic and the Church, in that order.